Prediction of Malignant Transformation of WHO II Astrocytoma Using Mathematical Models Incorporating Apparent Diffusion Coefficient and Contrast Enhancement - Wong, Alex Mun-Ching; Siow, Tiing Yee; Wei, Kuo-Chen; Chen, Pin-Yuan; Toh, Cheng Hong; Castillo, Mauricio (Frontiers in Oncology, 2021)
Malignant transformation (MT) of low-grade gliomas (LGGs) is the histopathologic progression of WHO grade II tumors to grade III or IV tumors. Increased contrast enhancement on MRI is frequently used as a surrogate marker for MT in clinical practice because of potential risks and costs associated with histopathologic confirmation. However, about 1/3 of LGGs with increasing contrast enhancement remain grade II, and this limited accuracy may cause misinterpretation of clinical outcomes. Reduced apparent diffusion coefficient (ADC) on MRI may be used to identify MT, but its reproducibility and accuracy are affected by tumor heterogeneity. We developed and validated a regression model based on clinical and imaging factors to predict MT in a group of patients with LGGs with increased contrast enhancement on follow-up MRI studies. On receiver operating characteristic curve analysis, the model (AUC 0.87) outperformed contrast enhancement size (AUC 0.67) or ADC (AUC 0.85) alone. With this proposed model incorporating widely used surrogate imaging markers, the accuracy of diagnosing MT of previously treated LGGs can be improved.